Sclerotherapy in pyogenic granuloma and mucocele - Jigna S Shah; Ashish F Ranghani (Wolters Kluwer Medknow Publications, 2018)
Aim and Objective: To evaluate the effect of intralesional injection of polidocanol for treating pyogenic granuloma and mucocele that commonly in the oral cavity. This study also aimed to analyze the effect of polidocanol in both lesions of various sizes. Materials and Methods: Fifteen clinically diagnosed cases of oral pyogenic granuloma (8 cases) and mucocele (7 Cases) were included in the study. After topical anesthesia application, 0.5-1 ml of polidocanol was injected using an insulin syringe into the lesion till the solution leaked out. Each patient was recalled after 1 week and evaluated; if the lesion did not resolve, second and third injections were given consecutively. Results: All 15 patients showed complete regression of the lesion after 1-3 consecutive injections in a weekly interval. Recurrence of one case of mucocele occurred. Conclusion: Sclerotherapy is simple, minimally invasive, economical, and of minimal discomfort to the patient; there is negligible blood loss, and less surgical expertise is required. Size of the lesion determines the number of weekly injections of sclerotherapy required for complete resolution of the lesion; however, numbers of injections do not depend on age, sex, and site of the lesion.